Introduction of machine translation into audiovisual translation teaching - Orel Kos, Silvana (ELOPE (Ljubljana), 2024)
Subtitling has long been the primary type of audiovisual translation in Slovenia. A steady increase in the production of audiovisual content, including English-speaking movies and TV series, along with the development of machine translation, have seen a growing need and opportunity for subtitling globally. The Department of Translation Studies (University of Ljubljana) has offered courses in subtitling to MA students for over twenty years. In the course of this time, teaching methods have been adapted to embrace new technologies. Recently, students have shown interest in incorporating machine translation into the subtitling course. The paper presents an analysis of a subtitling assignment in which students were asked to post-edit DeepL’s Slovene translation of English formatted movie subtitles. The post-edited subtitles were compared with the subtitles done by a group of students from scratch. The results show considerable differences in the students’ multimodal awareness and the overall quality of the subtitles between the two groups.
Keywords: AVT teaching; machine translation; multimodal awarenes; multimodalno zavedanje; podnaslavljanje; popravljanje strojnih prevodov; post-editing; poučevanje avdiovizualnega prevajanja; strojno prevajanje; subtitling